Untangling Culture Shock and Workplace Bullying using Organisational Support in Achieving Expatriate Adaptation - Ndagi, Abdullahi; Ali, Anees Janee (UUM PRESS, 2024)
Similar to other expatriate destinations, expatriates in Nigeria are susceptible to a myriad of issues. Nevertheless, empirical investigation to curb vicious actions against expatriates in Nigeria has been scarce and scanty. This study was conducted on the notion that organisational support moderates the negative effects of workplace bullying and culture shock on the adaptation of expatriates in Nigeria. It is a quantitative, correlational, and cross-sectional study based on responses gathered using a purposive sampling technique from 192 expatriates from 17 countries working in Nigeria. The PLS-SEM path modelling outcomes indicated that both culture shock and workplace bullying negatively and significantly affect both work and non-work domains of expatriate adaptation. On the contrary, the path coefficients and t-values obtained for the moderation of culture shock by organisational support are positive but weak. Consequently, the p-values were not statistically significant and H3 was not supported. The moderation of workplace bullying and adaptation by organisational support was negative and also weak, implying that H4 is also not supported. In order to forestall the burdens of adaptation on expatriates, multinational companies are encouraged to explore various support measures, including cross-cultural training and addressing workplace bullying, to facilitate smooth adaptation for expatriates